2004
DOI: 10.1152/jn.00840.2003
|View full text |Cite
|
Sign up to set email alerts
|

Activity in the Hypothalamus, Amygdala, and Cortex Generates Bilateral and Convergent Modulation of Pontine Gustatory Neurons

Abstract: Lundy, Robert F., Jr. and Ralph Norgren. Activity in the hypothalamus, amygdala, and cortex generates bilateral and convergent modulation of pontine gustatory neurons. J Neurophysiol 91: 1143-1157, 2004. First published November 19, 2003 10.1152/jn.00840.2003. Evidence suggests that centrifugal modulation of brain stem gustatory cells might play a role in the elaboration of complex taste-guided behaviors like conditioned taste aversion and sodium appetite. We previously showed that activity in one forebrain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
101
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(105 citation statements)
references
References 54 publications
3
101
0
1
Order By: Relevance
“…Neural pathways related to learning-memory formation are considered as plastic and dynamic networks and not as static wiring models, because feedback and feedforward interactions are known to exist in learning and specifically within the CTA circuitry (Katz et al, 2002;Lundy and Norgren, 2004). Furthermore, a hedonic neural circuit independent from sensory processes seems to be modified during CTA formation (Yamamoto et al, 1994a;Grancha et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Neural pathways related to learning-memory formation are considered as plastic and dynamic networks and not as static wiring models, because feedback and feedforward interactions are known to exist in learning and specifically within the CTA circuitry (Katz et al, 2002;Lundy and Norgren, 2004). Furthermore, a hedonic neural circuit independent from sensory processes seems to be modified during CTA formation (Yamamoto et al, 1994a;Grancha et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that both properties may be used to encode changes in concentration. We speculate that, in response to concentration changes, such varied behavior could be a consequence of the fact that GC receives (and transmits) information from other cortical and subcortical areas (Smith and Li, 2000;Lundy and Norgren, 2004) and that these areas will respond differentially to different tastants and concentrations of tastants. In particular, tastants such as quinine and sucrose possess different hedonic valences, so additional networks may be recruited to reflect different palatabilities (Small et al, 2003;Sewards, 2004).…”
Section: Codingmentioning
confidence: 99%
“…These forebrain nuclei likely have a role in gustatory modulation of the cells in the PbN. Indeed, electrophysiological investigations have reported that gustatory responses of pontine neurons are modulated by electrical stimulation of the LH, CeA, and GC in the hamster and the rat (11,35,39,40).The VPMpc, the third-order gustatory relay in the rodent, is less understood in several aspects (56,68,85,86). For example, whereas the afferent projections from the PbN to the VPMpc were well documented, the efferent projections from the VPMpc to the PbN were not demonstrated (4,21,64).…”
mentioning
confidence: 99%
“…These forebrain nuclei likely have a role in gustatory modulation of the cells in the PbN. Indeed, electrophysiological investigations have reported that gustatory responses of pontine neurons are modulated by electrical stimulation of the LH, CeA, and GC in the hamster and the rat (11,35,39,40).…”
mentioning
confidence: 99%